2011
DOI: 10.1038/nrn3111
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and epigenetic mechanisms of addiction

Abstract: Preface Investigations of long-term changes in brain structure and function that accompany chronic exposure to drugs of abuse suggest that alterations in gene regulation contribute importantly to the addictive phenotype. We review multiple mechanisms by which drugs alter the transcriptional potential of genes, from the mobilization or repression of the transcriptional machinery to epigenetics — including alterations in the accessibility of genes within their native chromatin structure and the regulation of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
781
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 876 publications
(857 citation statements)
references
References 145 publications
32
781
0
12
Order By: Relevance
“…Although GABAergic interneurons make up about 2% of all neurons in the NAc [41], GABA receptor agonists have been widely used to inactivate the NAc [42,43]. Infusion of one tenth of the regular doses of GABA receptor agonists into the NAcSh was effective in rescuing the novelty-seeking behavior of TLR4 -/-mice under motivational conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Although GABAergic interneurons make up about 2% of all neurons in the NAc [41], GABA receptor agonists have been widely used to inactivate the NAc [42,43]. Infusion of one tenth of the regular doses of GABA receptor agonists into the NAcSh was effective in rescuing the novelty-seeking behavior of TLR4 -/-mice under motivational conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Puisque les modifications épigénétiques se placent en aval de l'activité synaptique, elles ont la capacité d'intégrer un ensemble de signaux et de moduler la réponse à long terme d'un neurone en contrôlant l'expression des gènes, donc le degré de plasticité. Par ce contrôle, elles seraient en mesure d'imposer au neurone une réponse de drogue figurent à l'évidence des mécanismes de plasticité neuronale [6], qui concernent la modification de l'efficacité synaptique, mais aussi des changements de la morphologie des épines dendritiques, par exemple. D'un autre côté, vu les très nombreux mécanismes de plasticité sollicités en permanence durant le fonctionnement normal du cerveau, on peut se demander si la dépendance, qui implique une fixité du comportement, ne résulte pas plutôt d'un déficit de plasticité, voire d'une plasticité qui deviendrait figée en réponse aux drogues, au sein de structures cérébrales précises.…”
Section: La Dépendance Aux Droguesunclassified
“…Une complexité inouïe se dégage de l'ensemble de ces mécanismes. Puisque chaque modification est susceptible d'influencer les autres [35] et que cette régulation varie selon le gène considéré, il semble difficile d'invoquer un « code des histones », comme cela est parfois proposé [6,10,35]. Acétyler des histones revient à éliminer les charges positives des résidus lysine, donc à diminuer les interactions des histones avec l'ADN.…”
Section: Les Modifications Post-traductionnelles Des Histones L'acétunclassified
See 1 more Smart Citation
“…The transcriptional and epigenetic mechanisms of drug action on gene expression are well established, including alterations in transcription factors, histone tail modification, DNA methylation, and microRNAs. These changes contribute substantially to the neuronal adaptions that result from chronic drug exposure [5]. Jia et al [6] showed that miR-137 and miR-149 negatively regulate dopamine transporter (DAT) expression and dopamine transport at the post-transcriptional level in neural cells.…”
mentioning
confidence: 99%